Ehrlichia ruminantium (Ehrlichiaceae) infection rates and genotyping in Amblyomma species from southern Africa - (:unkn) unknown (My University, 2025)
Ticks are haematophagous ectoparasites of domestic and wild animals. With their vast geographical distribution and aptitude as vectors of a large variety of pathogens, they are ranked amongst the top two arthropod families of veterinary and medical concern. Amblyomma, the third largest genus in the Ixodidae, is important in southern Africa due to its vector competence for Ehrlichia ruminantium and other pathogens. Ehrlichia ruminantium, the causative agent of heartwater, a potentially lethal disease in ruminants, is classified as a notifiable disease by the World Organisation for Animal Health. Amblyomma species ticks were collected in five southern African countries from livestock and wildlife. They were morphologically identified to species level with taxonomic keys, and species identity was confirmed with molecular assays. Preliminary screening for E. ruminantium was conducted by targeting the pCS20 gene fragment. Genotyping of 39 E. ruminantium positives was obtained using Ampliseq technology. In total, 7,734 Amblyomma ticks were collected and identified as belonging to four species: Amblyomma eburneum, Amblyomma hebraeum, Amblyomma pomposum and Amblyomma variegatum. Ehrlichia ruminantium infection rates per country ranged from 7.1 % to 34.1 %. The genotyping analysis indicated the clustering of our sequences with strains Gardel, Welgevonden, Um Banein, Springbokfontein 4 and 2, Kwanyanga, and Blaauwkrans. The Ampliseq analysis was not effective in differentiating between strains found in southern Africa. This large study documents the genetic diversity and prevalence of E. ruminantium in ticks across southern Africa, highlighting implications for disease control and vaccine development.
Keywords: African Research